1992
DOI: 10.1073/pnas.89.16.7408
|View full text |Cite
|
Sign up to set email alerts
|

Serine tRNA complementary to the nonuniversal serine codon CUG in Candida cylindracea: evolutionary implications.

Abstract: In the asporogenc yeast Candida cylindracea, the codon CUG is read as serine instead of leucine. This is an unusual insance in which the amino acid ignment of a codon deviates from the universal code. To infer the evolutionary process of this change, the tRNA with the anticodon sequence CAG, which is complementary to and thus responsible for transltion of the codon CUG, has been identified. Indeed, this tRNA t tes an in-frame CUG codon in a synthetic mRNA as serine in an in vitro tntion system. The gene for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…Assuming that a similar signalling cascade might exist in C. albicans and that the corresponding homologous genes could be expressed in S. cerevisiae despite the deviation from universal translation rules for some Candida species (32,60,69), we were able to isolate a complementing C. albicans homolog of the S. cerevisiae SLT2 gene, suggesting that a signalling cascade homologous to the Pkc1-controlled cascade of S. cerevisiae is functional in this opportunistic fungus. The isolated gene, named MKC1, replaced the function of SLT2 in S. cerevisiae null mutants by restoring growth and preventing autolysis at 37ЊC, thus showing that the Candida gene is expressed in Saccharomyces cells.…”
Section: Discussionmentioning
confidence: 78%
“…Assuming that a similar signalling cascade might exist in C. albicans and that the corresponding homologous genes could be expressed in S. cerevisiae despite the deviation from universal translation rules for some Candida species (32,60,69), we were able to isolate a complementing C. albicans homolog of the S. cerevisiae SLT2 gene, suggesting that a signalling cascade homologous to the Pkc1-controlled cascade of S. cerevisiae is functional in this opportunistic fungus. The isolated gene, named MKC1, replaced the function of SLT2 in S. cerevisiae null mutants by restoring growth and preventing autolysis at 37ЊC, thus showing that the Candida gene is expressed in Saccharomyces cells.…”
Section: Discussionmentioning
confidence: 78%
“…Third, this modification is highly conserved among eukaryotes (Sprinzl et al 1998). Thus, 21 out of 23 characterized eukaryotic cytoplasmic tRNA Ser species have Um 44 , and the two exceptions are chicken tRNA Ser , which lacks the long variable loop and has A 44 , and tRNA Ser(CAG) from Candida cylindracea, which is specific for CUG leucine codons in this organism because of its altered genetic code and itself has unusual features in its primary structure (Yokogawa et al 1992 Ser uniquely labeled at U 44 (U44*Ser). Treatment with RNaseT1, RNaseA and calf intestinal phosphatase (CIP) yields Ump*G if U 44 is methylated and inorganic phosphate (P i ) if the substrate is unmodified.…”
Section: Introductionmentioning
confidence: 99%
“…In order to demonstrate the validity of this method, we selected a serine tRNA having the anticodon CAG (tRNASerCAG), corresponding to the universal leucine codon CUG, from Candida cylindracea [15,16]. We have already reported that the universal leucine codon CUG is read as serine in several Candida species by a specific serine tRNA corresponding to the codon CUG (tRNASerCAG) [17,18], following an experiment showing that the codon CUG can in fact be translated as serine in an in vitro translation with this serine tRNA using synthetic mRNA containing the in-frame CUG codons [15,16]. Here, we attempted to analyze the aminoacylated form of this serine tRNA in the cell to ensure that the tRNA is also charged with serine even in vivo.…”
Section: Introductionmentioning
confidence: 99%